Exposure to psychosocial factors at work and mental well¬being in Europe / Esposizione ai fattori psicosociali a lavoro e benessere mentale in Europa - Ardito, Chiara; d'Errico, Angelo; Leombruni, Roberto (La Medicina del Lavoro, 2014)
SUMMARY Background: Depression among workers is a major health concern and psychological work factors are considered important risk factors. Objectives: To investigate exposure to psychosocial work risk factors and prevalence of depressive symptoms in the European working population, and to identify the psychosocial work characteristics that predict them. Methods: The study is a secondary data analysis based on a sample of 33,907 European employees from the last edition of the European Working Condition Survey (EWCS 2010). The relationship between the outcome variable (depressive symptoms) and the predictors (psychosocial work factors) was analyzed using a multistage Poisson model, estimating genderspecific relative risks (RR) and 95 percent confidence intervals. Results: After adjustment for individual and work characteristics, countries and other psychosocial factors, among men the RR of depressive symptoms was significantly increased for exposure to intermediate psychological demands and to high demands for hiding emotions, whereas high skill discretion, high support from colleagues, high support from managers, high job rewards and high job security significantly decreased the risk. Among women, high psychological demands and intermediate emotional demands significantly enhanced the risk of depressive symptoms while high decision authority, intermediate support from colleagues, high support from managers, high social climate, high job rewards and high job security protected against risk. Conclusions: A high prevalence of depressive symptoms was found in the EWCS 2010, although with wide variations between countries. Several psychosocial factors at work were identified as risk factors for depressive symptoms, even after adjusting for workplace coexposures and other potential confounders. RIASSUNTO «Esposizione ai fattori psicosociali a lavoro e benessere mentale in Europa». Introduzione: La diffusione della depressione fra i lavoratori è un problema cruciale e le condizioni psicosociali di lavoro sono importanti fattori di rischio. Obiettivi: Analizzare l’esposizione a fattori psicosociali, l’incidenza di sintomi depressivi e studiarne l’associazione. Metodi: Analisi secondaria basata su un campione casuale rappresentativo di 33,907 lavoratori europei (EWCS 2010). La relazione fra fattori psicosociali e depressione è studiata con il modello di Poisson, stratificato per genere. Si presentano RR e IC al 95%. Risultati: Controllando per fattori confondenti quali la coesposizione ad altri fattori psicosociali, caratteristiche individuali e lavorative, fra gli uomini, il rischio di sintomi depressivi aumenta per livelli intermedi di domande psicologiche e per elevata necessità di nascondere le proprie emozioni, mentre elevate possibilità di utilizzare e sviluppare le proprie competenze, supporto sociale dei superiori e dei colleghi, elevate ricompense e sicurezza lavorativa lo riducono significativamente. Fra le donne, livelli elevati di domande psicologiche e intermedi di domande emozionali aumentano significativamente il rischio di depressione. Svolgono un ruolo protettivo un’elevata autonomia decisionale, un livello di supporto intermedio da parte dei propri colleghi ed elevato da parte dei superiori, un clima aziendale positivo e elevate ricompense e sicurezza lavorativa. Conclusioni: Si riscontra un’elevata prevalenza di depressione fra i lavoratori europei dell’EWCS 2010 e una ampia variabilità fra paesi. Diversi fattori psicosociali sul lavoro sono stati identificati come fattori di rischio dei sintomi depressivi, anche controllando per l’esposizione ai restanti fattori psicosociali e per altri potenziali confondenti.